2021
DOI: 10.1371/journal.pone.0258276
|View full text |Cite
|
Sign up to set email alerts
|

Three year clinical outcomes in a nationwide, observational, siteless clinical trial of atrial fibrillation screening—mHealth Screening to Prevent Strokes (mSToPS)

Abstract: Background Atrial fibrillation (AF) is common, often without symptoms, and is an independent risk factor for mortality, stroke and heart failure. It is unknown if screening asymptomatic individuals for AF can improve clinical outcomes. Methods mSToPS was a pragmatic, direct-to-participant trial that randomized individuals from a single US-wide health plan to either immediate or delayed screening using a continuous-recording ECG patch to be worn for two weeks and 2 occasions, ~3 months apart, to potentially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“… 19 The partly randomised mHealth Screening to Prevent Strokes (mSToPS) study suggested that active monitoring with a rhythm patch in high-risk individuals with AF without symptoms may reduce adverse outcomes over 3 years follow-up. 24 Outcome data of the currently published systematic screening trials Systematic ECG Screening for Atrial Fibrillation Among 75 Year Old Subjects in the Region of Stockholm and Halland, Sweden (STROKESTOP) 20 and Danish Atrial Fibrillation Detected by Continuous ECG Monitoring (LOOP) show controversial results. 25 Ongoing studies examine stroke rates, major bleeding, and mortality with different AF screening approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 The partly randomised mHealth Screening to Prevent Strokes (mSToPS) study suggested that active monitoring with a rhythm patch in high-risk individuals with AF without symptoms may reduce adverse outcomes over 3 years follow-up. 24 Outcome data of the currently published systematic screening trials Systematic ECG Screening for Atrial Fibrillation Among 75 Year Old Subjects in the Region of Stockholm and Halland, Sweden (STROKESTOP) 20 and Danish Atrial Fibrillation Detected by Continuous ECG Monitoring (LOOP) show controversial results. 25 Ongoing studies examine stroke rates, major bleeding, and mortality with different AF screening approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of Remote Heart Rhythm Sampling Using the AliveCor Heart Monitor to Screen for Atrial Fibrillation: The REHEARSE-AF study randomised ambulatory patients ≥65 years of age with stroke risk factors to twice-weekly single-lead iECG for 1 year and demonstrated the acceptance of this screening method and a possible benefit for stroke risk 19. The partly randomised mHealth Screening to Prevent Strokes (mSToPS) study suggested that active monitoring with a rhythm patch in high-risk individuals with AF without symptoms may reduce adverse outcomes over 3 years follow-up 24. Outcome data of the currently published systematic screening trials Systematic ECG Screening for Atrial Fibrillation Among 75 Year Old Subjects in the Region of Stockholm and Halland, Sweden (STROKESTOP)20 and Danish Atrial Fibrillation Detected by Continuous ECG Monitoring (LOOP) show controversial results 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study of cardiac rhythms focused specifically on SR and AF provides a basis for IH earbuds and for longer-term arrhythmia monitoring. The high sensitivity to detect AF during short time segments is especially critical for identifying and characterizing paroxysmal AF that may be particularly relevant in asymptomatic AF and for AF screening [21][22][23][24][25][26] . Future studies are underway to validate these findings in larger datasets and to include a variety of cardiac arrhythmias (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of early AF diagnosis on these findings remains unclear due to the observational nature of the study. 68 Two large studies investigated the ability of an irregular pulse notification from a photoplethysmogram-enabled smartwatch or band to identify a new diagnosis of AF in a predominantly middle-aged population. 33,34 These studies demonstrated a low prevalence of HR irregularity, and the diagnostic algorithms performed well with a positive predictive value of 0.84 to 0.92 for AF.…”
Section: Wearables In Clinical Carementioning
confidence: 99%